Yorkshire General Hospital (B) - Thompson, Kenneth R. (London : SAGE Publications: SAGE Business Cases Originals, 2020)
In Yorkshire General Hospital (A) the organization is facing intense market competition from nearby health care facilities. Without the funding levels the competitors have, Yorkshire General Hospital has to make some creative decisions to enhance its ability to compete without the resources to invest in expensive technology, new treatment centers, or new or expanded facilities.In Yorkshire General Hospital (B) we learn what the senior leadership team of Yorkshire General Hospital did to meet the challenges outlined in Part A of the case. Decisions are made to focus on building higher levels of associate (employee) engagement that will lead to more favorable interactions with physicians, patients and their families, and the local community. The hospital builds a higher level of professionalization of its nursing staff through training programs and hiring specialty staff with whom the nursing staff can consult. The case demonstrates the value of developing a competency in a more professional level of performance, which leads to higher-quality interactions and positive relationships with the major stakeholders in the organization. Important to this change is that senior leadership helped to create a focus on key mission, vision, and value statements that would build a strong employee engagement focus that supports excellent care for patients.Students must evaluate the approaches used by Yorkshire General Hospital and how hospital staff might implement some of the proposed changes.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Hospitals -- Business management -- Case studies; Marketing -- Management -- Case studies; Hospitals -- Employees -- Training of -- Case studies; Hospital care -- Evaluation -- Case studies